Color Blind Illusion / Hasfariza Abu Hassan - Abu Hassan, Hasfariza (2001)
This Color Blind Illusion is a modern version of the famous three shell game. This project otters the use of single pole single trough switches to control any one of all devices. This circuit uses simple electronic devices such as integrated circuits, diodes, resistors and capacitors. The flip-flop circuit is used as a set/reset network for the flip-flop circuits. The light Emitting Diode used in the circuit are dual color-green and red The Schmitt trigger inverter concept is used to provide some delay in output and the magnetic switches will toggle the LED from green to red or vice versa.